(untitled) (Medicine Today, 2026)
Introduction: Mandibular third molar can causes both localized and regional complications due to its frequently abnormal positioning. This pathological positioning combined with its problematic eruption, often leads to several pathologies affecting adjacent teeth—most notably, the second mandibular molar. Materials & Methods: This is a prospective study that was conducted in the Department of Oral and Maxillofacial Surgery, Military Dental Centre, Savar Cantonment, Dhaka, Bangladesh from July 2024 - June 2025. The study population comprised of consented consecutive subjects requiring third molar extraction during the study period. To ensure diagnostic validity in this study, radiographic findings were verified with clinical records, which were collected on standard forms as part of the routine examination process. Results: There were no statistically significant differences of prevalence of impaction/not impaction (p=0.726), angulations (p=0.308) and side (p=0.208) of impaction among the study population. Pathologic conditions of second molars were almost common in male vs female (p= 0.478). And no statistical significance differences of pathologic condition of second molar were due to angulations (0.084) and impactions (0.774) were seen. The grossly carious second molars that were restorable we restore them either by restoration (18%) or root canal treatment (RCT) (14%) according to pulp pathological condition. But the non restorable were extracted (13%). Conclusion: Impacted mandibular third molar may causes carious lesions and periodontal disease in the adjacent second molar. Early identification and appropriate surgical management of impacted third molars can play a crucial role in preventing damage to the second molars. Medicine Today 2026, Vol.38 (1): 37-40